Whey protein but not collagen peptides stimulate acute and longer-term muscle protein synthesis with and without resistance exercise in healthy older women: a randomized controlled trial - Oikawa, Sara Y (Am J Clin Nutr, 2020)
BACKGROUND: Aging appears to attenuate the response of skeletal muscle protein synthesis (MPS) to anabolic stimuli such as protein ingestion (and the ensuing hyperaminoacidemia) and resistance exercise (RE). OBJECTIVES: The purpose of this study was to determine the effects of protein quality on feeding- and feeding plus RE–induced increases of acute and longer-term MPS after ingestion of whey protein (WP) and collagen protein (CP). METHODS: In a double-blind parallel-group design, 22 healthy older women (mean ± SD age: 69 ± 3 y, n = 11/group) were randomly assigned to consume a 30-g supplement of either WP or CP twice daily for 6 d. Participants performed unilateral RE twice during the 6-d period to determine the acute (via [(13)C(6)]-phenylalanine infusion) and longer-term (ingestion of deuterated water) MPS responses, the primary outcome measures. RESULTS: Acutely, WP increased MPS by a mean ± SD 0.017 ± 0.008%/h in the feeding-only leg (Rest) and 0.032 ± 0.012%/h in the feeding plus exercise leg (Exercise) (both P < 0.01), whereas CP increased MPS only in Exercise (0.012 ± 0.013%/h) (P < 0.01) and MPS was greater in WP than CP in both the Rest and Exercise legs (P = 0.02). Longer-term MPS increased by 0.063 ± 0.059%/d in Rest and 0.173 ± 0.104%/d in Exercise (P < 0.0001) with WP; however, MPS was not significantly elevated above baseline in Rest (0.011 ± 0.042%/d) or Exercise (0.020 ± 0.034%/d) with CP. Longer-term MPS was greater in WP than in CP in both Rest and Exercise (P < 0.001). CONCLUSIONS: Supplementation with WP elicited greater increases in both acute and longer-term MPS than CP supplementation, which is suggestive that WP is a more effective supplement to support skeletal muscle retention in older women than CP. This trial was registered at clinicaltrials.gov as NCT03281434.